Analisis dan Strategi Penanganan Risiko Supply Chain Pada PT. Batik Banten Indonesia Menggunakan AHP dan FMECA - Bahauddin, Achmad; Minata, Prima Ratna; Arina, Faula (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
Batik is one of the cultural assets that must be preserved because it plays an important role in the local economy. At PT. Batik Banten there are risks in every activity of the supply chain, so should receive appropriate treatment due to the risks that arise can make the supply chain activities are not going well. PT. Batik Banten supply chain activity consists of the purchase of raw materials, the production process, the distribution process, and the sales process. The purpose of this study are to identify the risks that arise in the supply chain of Batik Banten products, to determine the critical risks in the supply chain of Batik Banten products and to propose risk management strategies at critical risk factors. The method for solving the problem in this research is integration of AHP (Analytical Hierarchy Process) and FMECA (Failure Mode, Effects and Criticality Analysis) to determine the value of the RPN (Risk Priority Number) based on the weight value/WRPN (Weighted Risk Priority Number). Based on interviews with the commissioners of Batik Banten obtained 24 variables of risk, from the calculation of the critical value obtained three risks that must be handled, i.e supplier poor quality with WRPN value 21.6973, volatile customer demand with WRPN value 15.7580, and variability in production process with WRPN value 9.0452. To mitigate the risks of Batik Banten supply chain have been proposed risk management strategies that recommended, i.e evaluating the performance of suppliers, predicting demand based on historical data of sales and perform quality control in the production process.